STEM and ICT Education in Intelligent Environments - Kanematsu, Hideyuki; M. Barry, Dana (Intelligent Systems Reference Library, 2016)
This book combines information communication technology (ICT) with the creative interdisciplinary teaching approach known as STEM (science, technology, engineering, and mathematics). It introduces STEM and Creative Education and shows (through examples and creative activities) the importance and impact that ICT has for STEM and modern education.  The book describes the audio visual classroom, the use of the Internet, Social Networking and STEM, and provides STEM lessons for both the real and virtual worlds. Instructors will find this unique textbook to be very useful with students, of various ages, in creative education and engineering classes. This special book offers something for everyone. It serves as a guide for teachers in charge of science fairs and creative classes, especially those which require STEM education. It also includes activities to help develop creative thinking and problem-solving skills, and prepares students who plan to become teachers and mentors of thefuture. Readers in general can simultaneously enjoy and learn about ICT's impact on STEM and modern education.  In addition, e-learning designers and administrators who want to introduce e-learning systems into their organizations can refer to this book as a reference and a resource. The book complements most e-learning and ICT education books which generally focus too much on technical issues.   .